PENERAPAN MODEL ALTERNATIF PENEGAKAN HUKUM TINDAK PIDANA KORUPSI SEBAGAI JALAN PEMULIHAN KERUGIAN KEUANGAN NEGARA - Justicia, Yudistira (Bahasa Indonesia, 2022)
The current perspective on eradicating corruption still prioritizes corporal punishment or imprisonment for perpetrators of corruption instead of using the perspective of returning state finances, this perspective is based on the view of retributive justice theory which is the legal basis for eradicating corruption, the theory of retributive justice is irrelevant to the main goal of corruption eradication law in Indonesia which was built with the spirit of recovering state financial losses, this is far more important than prioritizing imprisonment for perpetrators of corruption, namely the recovery of state financial losses. justice to maximize state financial returns in criminalizing corruptors in Indonesia through asset confiscation using both criminal and civil channels. By using normative juridical research methods. This study concludes that the concept of restorative justice in sentencing perpetrators of corruption can be implemented in the form of strengthening norms for recovering state losses without prejudice to the deprivation of independence of perpetrators which aims to provide a deterrent effect on perpetrators of corruption crimes and confiscating assets against perpetrators of corruption both through criminal and civil channels